Resolusi Konflik Lahan Antara Peladang Pendatang dan Peladang Setempat di Kecamatan Batang Merangin Kabupaten Kerinci - Neza Helpitia (Faculty of Social Science, Universitas Negeri Padang, 2017)
This study aimed to determine the factors causing land conflicts and how conflict management efforts applied in the resolution of land conflicts between immigrant farmers and local cultivators in Batang Merangin District, Kerinci Regency. This study was a qualitative research with descriptive method. Data in this study were collected through interview and documentation study. Informants in this study were determined by purposive sampling technique and snowball sampling. Data were analyzed with interactive analysis model. The results of this study indicated that factors causing land conflicts include: a) seizing land resources between immigrant farmers and local cultivators; b) poor communication between immigrant farmers and local cultivators; c) the social jealousy of local cultivators on the success of immigrant farmers in cultivating the land; d) theft, looting, incarceration, and burning of farm houses belonging to immigrant farmers by local cultivators. Conflict management in this case were carried out in two ways, namely negotiation and mediation by local government of Kerinci Regency.